Clinical and genomic characterization of chemoradiation-resistant HPV-positive oropharyngeal squamous cell carcinoma - Guo, Theresa; Zamuner, Fernando; Ting, Stephanie; Chen, Liam; Rooper, Lisa; Tamayo, Pablo; Fakhry, Carole; Gaykalova, Daria; Mehra, Ranee (Frontiers in Oncology, 2024)
Introduction: Most patients with HPV-positive oropharyngeal squamous cell carcinoma (OPSCC) have an excellent response to chemoradiation, and trials are now investigating de-escalated treatment. However, up to 25% of patients with HPV-positive OPSCC will experience recurrence, and up to 5% will even progress through primary treatment. Currently, there are no molecular markers for identifying patients with poor prognosis who would be harmed by de-escalation. Herein, we report the clinical and genomic characteristics of persistent HPV-positive OPSCC after definitive platinumbased chemoradiation therapy. Methods: Patients with HPV-positive OPSCC treated with curative intent platinumbased chemoradiation between 2007 to 2017 at two institutions and persistent locoregional disease were included. We evaluated clinical characteristics, including smoking status, age, stage, treatment, and overall survival. A subset of 5 patients had tissue available for targeted exome DNA sequencing and RNA sequencing. Genomic analysis was compared to a previously published cohort of treatment responsive 47 HPV+ OPSCC tumors after batch correction. Mutational landscape, pathway activation, and OncoGPS tumor states to characterize these tumors. Results: Ten patients met inclusion criteria. Tumor and nodal stages ranged from T1 to T4 and N1 to N2 by AJCC 8th staging. All patients were p16 positive by IHC, and 8 with available ISH were confirmed to be HPV-positive. One-year overall survival from the time of diagnosis was 57%, and two-year overall survival was 17%. TP53 mutations were present in 3 of 5 (60%) persistent tumors compared to 2% (1 of 47) treatmentresponsive HPV-positive tumors (p=0.008). Other genes with recurrent mutations in persistent HPV-positive OPSCC tumors were NF1, KMT2D, PIK3C2B, and TFGBR2. Compared to treatment-responsive HPV-positive tumors, persistent tumors demonstrated activation of DNA repair, p53, EMT, MYC, SRC, and TGF-beta signaling pathways, with post treatment samples demonstrating significant activation of the PI3K-EMT-Stem pathways compared to pre-treatment samples. Conclusions: Chemoradiation-resistant HPV-positive OPSCC occurs infrequently but portends a poor prognosis. These tumors demonstrate higher rates of p53 mutation and activation of MYC, SRC, and TGF-beta pathways. Comparison of tumors before and after treatment demonstrate PI3K-EMT-Stem pathways post treatment in HPVpositive tumors with persistent disease after platinum based chemoradiation.